Recurrent primary pulmonary anaplastic B-cell lymphoma in a 35-year-old patient treated with radical resection: A case report. - George Bashour; Muhsen Issa; Saddik Haddad; Gabi Kafa; Hussein Kaada; Samer Rajab; Ali Daoud; Rabab Salloum (Current Problems in Cancer: Case Reports)
Background: Primary pulmonary lymphoma (PPL) is a lymphoid proliferation in the lung parenchyma and/or bronchi of a patient with no extrapulmonary lesion within 3 months of diagnosis. Diffuse large B-cell lymphoma (DLBCL) accounts for 10 % of all PPL cases, and only a very minor number of them present with an anaplastic morphologic variant. Case presentation: We report a 35-year-old female patient who presented with shortness of breath, cough, anorexia, weight loss, fever of unknown origin, and night sweats. The patient was diagnosed with primary pulmonary anaplastic DLBCL and put on rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) regimen. She achieved remission according to the PET scan results; however, the symptoms recurred one year later, and a CT scan confirmed the regrowth of the tumor. The patient refused further chemotherapy and repeated the biopsy at another center, and she was diagnosed with Hodgkin lymphoma and was placed on ifosfamide, carboplatin, and etoposide (ICE) and rituximab, dexamethasone, cytarabine, and cysplatin (RDHAP) protocols for 9 months, which did not improve her condition. Finally, a PET scan revealed that the lesion was limited to the lung with no visible metastases or lymph node involvement, and radical surgery was performed to excise the tumor. A new IHC panel was ordered because of the conflicting reports, and it showed matching results to the first diagnosis, except for a negative CD20 result, which was attributed to rituximab in the patient's chemotherapy. A 2-year follow-up revealed no lesions or recurrence. Conclusion: DLBCL is an uncommon cause for primary lung lymphomas, but high clinical suspicion must be maintained when assessing such tumors, even among younger individuals. More studies should be done to investigate the best treatment option for the anaplastic variant of DLBCL.